2011
DOI: 10.1016/j.jacc.2011.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Associated With Surgical and Transcatheter Treatment of Aortic Stenosis

Abstract: Stroke is a potential complication of treating patients with aortic stenosis via surgical aortic valve replacement (AVR), transcatheter aortic valve replacement (TAVR), and balloon aortic valvuloplasty. Because there are limited and heterogeneous data on the incidence, risk factors, and outcomes of stroke among patients being treated for aortic stenosis, we performed a comprehensive review of the literature. The risk of stroke after AVR in the general population is approximately 1.5%, and the risk is increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
79
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(86 citation statements)
references
References 62 publications
(66 reference statements)
3
79
0
4
Order By: Relevance
“…That complication might be related to atheroembolism of plaques in the ascending aorta and aortic arch, embolization of calcified debris of native aortic valve leaflets, thromboembolism originating from the valvular prosthesis, and the occasional occurrence of atrial fibrillation, as might have occurred in one of our patients. In the PARTNER trial, only approximately half of the cases of stroke occurred during the procedure, which, along with our findings, raise the question about the efficacy of protective devices against cerebral embolism when used only at the occasion of prosthesis implantation 8,10,23 .…”
Section: Discussionmentioning
confidence: 56%
“…That complication might be related to atheroembolism of plaques in the ascending aorta and aortic arch, embolization of calcified debris of native aortic valve leaflets, thromboembolism originating from the valvular prosthesis, and the occasional occurrence of atrial fibrillation, as might have occurred in one of our patients. In the PARTNER trial, only approximately half of the cases of stroke occurred during the procedure, which, along with our findings, raise the question about the efficacy of protective devices against cerebral embolism when used only at the occasion of prosthesis implantation 8,10,23 .…”
Section: Discussionmentioning
confidence: 56%
“…Although the clinical relevance of these DWI lesions remains uncertain, they may cause decline in cognitive function as suggested by previous reports on silent cerebral lesions involving patients other than the typical TAVR patients [11,12,22]. For instance, the population-based Rotterdam Scan Study showed that elderly people with silent brain infarcts have an increased risk of dementia and a steeper decline in cognitive function than those without such lesions [11,12,22]. Therefore, based on these previous reports, the high frequency of ischemic lesions on post-TAVR cerebral imaging calls for procedural and technical developments to reduce the risk of peri-procedural embolization.…”
Section: Discussionmentioning
confidence: 90%
“…Recent data have suggested comparable or higher risk of stroke after transcatheter AVR compared with conventional AVR. [20][21][22][23] This is concerning in the context of observational studies demonstrating an incidence of cerebrovascular lesions, as detected by MRI, of >70% after transcatheter AVR. 24 Prevention of ischemic stroke is, therefore, of key importance for continued safe expansion of transcatheter AVR and conventional AVR.…”
Section: Discussionmentioning
confidence: 99%